Roles of NRF2 in Fibrotic Diseases: From Mechanisms to Therapeutic Approaches - Hao, Wenlong; Li, Minghao; Cai, Qingmin; Wu, Shiying; Li, Xiangyao; He, Quanyu; Hu, Yongbin (Frontiers in Physiology, 2022)
Fibrosis is a persistent inflammatory response that causes scarring and tissue sclerosis by stimulating myofibroblasts to create significant quantities of extracellular matrix protein deposits in the tissue. Oxidative stress has also been linked to the development of fibrosis in several studies. The nuclear erythroid 2-related factor 2 (NRF2) transcription factor controls the expression of several detoxification and antioxidant genes. By binding to antioxidant response elements, NRF2 is activated by oxidative or electrophilic stress and promotes its target genes, resulting in a protective effect on cells. NRF2 is essential for cell survival under oxidative stress conditions. This review describes Kelch-like epichlorohydrin-associated protein 1 (KEAP1)/NRF2 signaling mechanisms and presents recent research advances regarding NRF2 and its involvement in primary fibrotic lesions such as pulmonary fibrosis, hepatic fibrosis, myocardial fibrosis, and renal fibrosis. The related antioxidant substances and drugs are described, along with the mechanisms by which KEAP1/NRF2 regulation positively affects the therapeutic response. Finally, the therapeutic prospects and potential value of NRF2 in fibrosis are summarized. Further studies on NRF2 may provide novel therapeutic approaches for fibrosis.